Textbook on the Bharatiya Sakshya Adhiniyam, 2023 - Monir, M. (Gurgaon LexisNexis, 2024)
Introducing Lexis Nexis's comprehensive textbook on The Bharatiya Sakshya Adhiniyam, 2023, authored by the esteemed Chief Justice M Monir. This meticulously crafted volume delves into the intricacies of the Indian Evidence Act, providing an in-depth analysis and expert insights. Designed to be an indispensable resource for legal professionals, students, and scholars alike, this textbook offers a comprehensive understanding of evidentiary rules and their practical application. With its clear and concise language, it elucidates complex concepts, making it an invaluable companion in navigating the nuances of the legal system. Enhance your knowledge, sharpen your skills, and stay ahead in the dynamic field of law with this authoritative textbook.
Keywords: New Law; Bharatiya Sakashya Adhiniyam